Laboratory and scaled up evaluation of cis-permethrin applied as a new ultra low volume formulation against Aedes aegypti (Diptera: Culicidae) - Seccacini, Emilia Ana (2006)
Ultra low volume (ULV) aerial spraying is a common methodology for spatial treatments for Aedes aegypti (L.) control. Previous studies from our laboratory indicated that the cis isomer of permethrin has an excellent efficacy for vector control, in particular for Triatoma infestans. It was of interest to determine the efficacy of this pure isomer in a ULV water-based formulation for adult A. aegypti control, since both vectors usually are found together in South America. A method is presented to make a quick measure at laboratory level of the knock down effect (KT50) of a new EC water-based formulation of cis-permethrin, in a small Peet Grady chamber of 0.34 m3, with a specially designed glass sprayer. A deltamethrin standard ULV formulation "CISLIN" was used for comparison. cis-Permethrin showed a significantly lower KT50 value than deltamethrin (7.50 and 9.65 min, respectively). When the mosquitoes were introduced into the chamber 10 min after spraying KT50 values were almost equal (15.59 and 15.88 min, respectively). In scaled up bioassays the ULV formulation of cis-permethrin showed 100% mortality of A. aegypti adult mosquitoes at the beginning of the treatment (t = 0) and some mortality at 1 h post treatment of freshly introduced mosquitoes. It was concluded that cis-permethrin could be an excellent tool for control of A. aegypti and other vectors of medical importance, with fewer side effects and better cost-effectiveness than with the cyanopyrethroids.